Study on fracture analysis of rotor blade in thermal power plant. Issue 1 (1st December 2022) - Lyu, Lei; Tu, Anqi; Wang, Yingjun
Abstract: The comprehensive failure analysis of the fractured LP rotor blade was carried out by means of appearance morphology analysis, SEM morphology analysis, mechanical property analysis, chemical composition analysis and microstructure detection. The results show that the second and last stage blades at the low-pressure rotor turbine side are damaged by mechanical collision, resulting in damage and deformation at the steam outlet side of the blades and generating stress concentration areas. The blades are prone to generate crack sources in the stress concentration areas of mechanical damage under the working load, and the cracks continue to expand on the condition of alternative stress, eventually leading to fatigue cracking and fracture of the blades. It is recommended to carefully check the blades at other positions of the LP rotor and deal with the mechanical damage and cracking problems in time. Secondly, foreign matters shall be prevented from entering the turbine with the steam to damage the blades, and the fixed parts inside the cylinder shall be ensured to be firm and not fall off, so as to prevent the recurrence of similar blade fracture.